2019
DOI: 10.1111/bjh.16106
|View full text |Cite
|
Sign up to set email alerts
|

Late relapse in patients with diffuse large B‐cell lymphoma: impact of rituximab on their incidence and outcome

Abstract: Diffuse large B-cell lymphoma (DLBCL) constitutes 25-35% of all non-Hodgkin lymphomas in Western countries. Approximately two thirds of the patients can be cured with standard immuno-chemotherapy. Most relapses occur within 1-2 years from diagnosis, however, the occurrence of relapses after 5 years or more has been described. We aimed at defining the incidence and clinical features of late relapses. Data of 1113 DLBCL patients were analysed. Among the 196 patients relapsing after a first complete remission, 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Given that it remains unclear which therapies may be useful in patients who have a relapse after the receipt of axi-cel, these additional data, together with real-world outcomes and clinical trials, may help inform treatment decisions in the future. 32 Whereas the majority of patients with large B-cell lymphoma have a relapse less than 12 months after the receipt of induction therapy in the post-rituximab era, 33,34 this trial did not enroll patients with large B-cell lymphoma relapse that occurred more than 12 months after the receipt of induction therapy. Relapses occurring later after induction therapy are generally associated with a greater probability of response to second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that it remains unclear which therapies may be useful in patients who have a relapse after the receipt of axi-cel, these additional data, together with real-world outcomes and clinical trials, may help inform treatment decisions in the future. 32 Whereas the majority of patients with large B-cell lymphoma have a relapse less than 12 months after the receipt of induction therapy in the post-rituximab era, 33,34 this trial did not enroll patients with large B-cell lymphoma relapse that occurred more than 12 months after the receipt of induction therapy. Relapses occurring later after induction therapy are generally associated with a greater probability of response to second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes depend on the relapse timing, as patients with early relapse show significantly poor compared to patients with late relapse [ 19 ]. For instance, in the CORAL study, patients with the relapsed disease within 12 months showed substantially lower response rate (46% vs. 88%), 3-year event-free survival rate (20% vs. 45%), and 3-year OS rate (39% vs. 64%) compared to patients with relapsed disease after 12 months when treated with rituximab combined with either ICE or DHAP [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second-line treatment was presumed to be for relapsed disease in 9% and for primary refractory disease in 7%. The reported incidence of relapsed/refractory DLBCL patients ranges between 17% and 30%, with up to 10% after EFS24 ( 15 , 18 , 38 , 61 , 62 ). This discrepancy with our cohort probably relies on 2 main factors.…”
Section: Discussionmentioning
confidence: 99%